Effect Of Competitors And Covid-19 Pandemic On Stock Prices Of Reinsurance Companies 2016-2020 - Santi Yuliati Fikri; Imam Hidayat (Universitas Islam Lamongan, 2022)
This research was conducted to determine the influence of competitors and Covid-19 which is believed to have contributed to the decline in insurance stocks. This study also aims to determine the impact of the decline in Indonesian stocks and their changes in recent years. The type of research used is descriptive quantitative research. Sources of data used are secondary data from advertisers, the Central Bureau of Statistics from annual reports and research documents about insurance. The type of data used is time series, the data is taken sequentially from 2016-2020. The type of data collection method used is the documentary method. The results showed that there was no influence between the competitor variables and covid-19 on stock prices at PT. Indonesian Reinsurance. On the other hand, the competitor variable has a positive effect on stock prices, while the Covid-19 variable has a negative effect on stock prices.